Adaptive Exponential Synchronization of Coupled Complex Networks on General Graphs - Song Liu; Xianfeng Zhou; Wei Jiang; Yizheng Fan (Abstract and Applied Analysis)
We investigate the synchronization in complex dynamical networks, where the coupling configuration corresponds to a weighted graph. An adaptive synchronization method on general coupling configuration graphs is given. The networks may synchronize at an arbitrarily given exponential rate by enhancing the updated law of the variable coupling strength and achieve synchronization more quickly by adding edges to original graphs. Finally, numerical simulations are provided to illustrate the effectiveness of our theoretical results.